Composite polymer solid electrolyte material and preparation method and application thereof
Patent Information
- Application Number
- CN202611149961.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-20
AI Technical Summary
[0008]本发明的目的就是提供一种复合聚合物固态电解质材料及其制备方法和应用,用于解决现有锂金属电池中聚合物固态电解质室温离子电导率低、锂金属负极界面不稳定以及枝晶生长难以有效抑制等问题
1. 本发明通过引入硒化铌构建复合结构,有效提高PVDF基固态电解质的室温离子电导率;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid electrolyte materials technology, and relates to a composite polymer solid electrolyte material, its preparation method and application. Background Technology
[0002] In recent years, with the rapid development of high-energy-density energy storage technologies, the next generation of electrochemical energy storage systems, represented by lithium metal batteries, has received widespread attention. Lithium metal anodes are particularly noteworthy due to their extremely high theoretical specific capacity (3860 mAh g⁻¹). -1 The lowest possible electrode potential is considered an important direction for realizing the next generation of high-energy-density batteries. However, traditional lithium metal batteries usually rely on organic liquid electrolyte systems, which are prone to serious dendrite growth problems during actual charge and discharge processes, leading to safety hazards such as separator puncture, internal short circuits, and thermal runaway. At the same time, liquid electrolytes also have problems such as volatility, leakage, and violent interfacial side reactions, which seriously limit their commercial application.
[0003] Against this backdrop, solid-state electrolytes are considered one of the key technological pathways to address the safety and stability issues of lithium metal batteries. Among them, polymer solid-state electrolytes have shown significant application potential in lithium metal battery systems due to their excellent flexibility, good film-forming properties, and good contact ability with the electrode interface. In particular, polymer materials, represented by polyvinylidene fluoride (PVDF) and its copolymers, possess high chemical stability and mechanical strength, which can suppress the disordered growth of lithium dendrites to a certain extent, thereby improving battery cycle stability. However, due to their high crystallinity and limited chain segment mobility, these materials exhibit low lithium-ion transport efficiency at room temperature, and their ionic conductivity is typically difficult to exceed 10. -4 The S / cm ratio is insufficient to meet the actual requirements of high-rate lithium metal batteries.
[0004] Currently, to improve the ion transport performance of polymer solid electrolytes, inorganic fillers (such as silicon dioxide, titanium dioxide, and various lithium-ion conductor materials) are usually introduced to regulate the polymer crystal structure, increase the proportion of amorphous regions, and thus promote ion migration.
[0005] Prior art CN116130758A discloses an electrolyte for dense polymer-based solid-state lithium batteries. The electrolyte includes a lithium salt, an organic solvent, a polyvinylidene fluoride polymer, and molybdenum diselenide. The PVDF-based solid-state electrolyte prepared by this invention uses molybdenum diselenide as a filler, resulting in significantly improved densification. The content of β-phase PVDF, the dielectric constant of the electrolyte, the ionic conductivity, the ion migration activation energy, and the oxidation resistance window are all improved.
[0006] However, these fillers mainly improve the transport environment through physical structure adjustment, which has limited effect on improving the lithium salt dissociation ability. At the same time, it is difficult to form a continuous and efficient ion transport channel. Therefore, the overall conductivity improvement effect is still limited, and the improvement in the stability of the lithium metal anode interface is insufficient.
[0007] Based on the above problems, it is necessary to develop a polymer solid electrolyte system that simultaneously possesses high ionic conductivity, excellent interfacial stability, and good mechanical properties. Summary of the Invention
[0008] The purpose of this invention is to provide a composite polymer solid electrolyte material, its preparation method, and its applications, to address the problems of low room-temperature ionic conductivity, unstable lithium metal anode interface, and difficulty in effectively suppressing dendrite growth in existing lithium metal batteries. This invention introduces niobium selenide (NbSe2) functional material into a PVDF matrix. Through its unique two-dimensional layered structure and interfacial electronic regulation characteristics, it can promote lithium salt dissociation while reducing polymer crystallinity and optimizing lithium ion migration pathways. This is expected to achieve a synergistic improvement in ion transport performance and interfacial stability, providing a new material system and technical path for high-performance lithium metal solid-state batteries.
[0009] The objective of this invention can be achieved through the following technical solutions: The first aspect of the present invention provides a method for preparing a composite polymer solid electrolyte material, comprising the following steps: mixing niobium selenide (NbSe2), a polymer, and a lithium salt in a solvent, coating, and drying to obtain the composite polymer solid electrolyte material.
[0010] In some specific embodiments, the niobium selenide layered material is used.
[0011] In some specific embodiments, the polymer is at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, or polyacrylate.
[0012] In some specific embodiments, the mass ratio of niobium selenide, polymer, and lithium salt is (0.01~0.4):1:0.028.
[0013] In some specific embodiments, the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bisfluorosulfonylimide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate, lithium difluorophosphate, and lithium tetrafluoroborate.
[0014] In some specific embodiments, the solvent is selected from at least one of tetrahydrofuran, acetonitrile, N,N-dimethylformamide, or N-methylpyrrolidone.
[0015] In some specific embodiments, the coating includes scraping or casting.
[0016] In some specific embodiments, the drying is carried out by vacuum drying, with a drying temperature of 50~80℃ and a drying time of 12~48 h.
[0017] A second aspect of the present invention provides a composite polymer solid electrolyte material, which is prepared by the method described above.
[0018] A third aspect of the present invention provides an application of the composite polymer solid electrolyte material as described above, including using the composite polymer solid electrolyte material to prepare a solid metal battery.
[0019] In some specific embodiments, the positive electrode of the solid metal battery is a lithium iron phosphate positive electrode or a nickel-cobalt-manganese ternary positive electrode; the negative electrode is one of an alkali metal negative electrode, a graphite negative electrode, a hard carbon negative electrode, a silicon-carbon negative electrode, or a phosphorus material negative electrode; preferably, it is a lithium negative electrode.
[0020] In this invention, niobium selenide two-dimensional material forms a uniformly dispersed structure in a PVDF matrix. On the one hand, it reduces the crystallinity of PVDF and increases the proportion of amorphous phase through interfacial interactions, thereby enhancing the mobility of polymer chain segments. On the other hand, it promotes the dissociation of lithium salt, increasing the concentration of free lithium ions in the system and fundamentally improving ion transport efficiency. Simultaneously, the local polarization effect formed at the interface between niobium selenide and the polymer can construct a built-in electric field, accelerating lithium ion migration kinetics and reducing interfacial transport impedance.
[0021] Furthermore, this composite structure can effectively improve the interfacial contact state between the solid electrolyte and the lithium metal anode, suppress the disordered growth of lithium dendrites, reduce interfacial side reactions, and thus improve the cycle stability and safety performance of the battery.
[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention effectively improves the room-temperature ionic conductivity of PVDF-based solid electrolytes by introducing niobium selenide to construct a composite structure; 2. This invention enhances the dissociation ability of lithium salts and improves the lithium-ion transference number and transport efficiency; 3. This invention improves the stability of the lithium metal anode interface, inhibits dendrite growth, and enhances battery safety; 4. The preparation process of this invention is simple, and it can be prepared on a large scale using the solution method, which has good prospects for engineering applications. Attached Figure Description
[0023] Figure 1 The XRD pattern of NbSe2 obtained in Example 1 of this invention; Figure 2The images shown are SEM images of PVDF and PVDF-NbSe2 obtained in Example 1 of this invention. Figure 3 The variable rate performance diagram of the PVDF-NbSe2 full cell obtained in Example 1 of the present invention is shown. Figure 4 The graph shows the long-cycle performance test of Li|PVDF-NbSe2|NCM811|Li obtained in Example 1 of the present invention at 30 °C for 2C. Figure 5 The graph shows the long-cycle performance test of Comparative Example 1 of the present invention, Li|PVDF|NCM811|Li, at 30 °C for 2C. Figure 6 The PVDF-NbSe2 obtained in Example 1 of this invention at 0.1 mA cm 2 Voltage-time curve at current density. Detailed Implementation
[0024] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0025] For simplicity, this invention only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, although not explicitly stated, each point or individual value between the endpoints of the range is included within that range. Therefore, each point or individual value can be used as its own lower or upper limit and combined with any other point or individual value, or combined with other lower or upper limits, to form a range not explicitly stated. In the description of this invention, it should be noted that, unless otherwise stated, "above" includes the stated number, and "multiple" in "one or more" means two or more.
[0026] The foregoing description of this application is not intended to describe every disclosed embodiment or implementation of the invention. Instead, the following description provides more specific examples of exemplary embodiments. Throughout the application, guidance is provided through a series of embodiments that can be used in various combinations. In each example, the examples are listed only as representative groups and should not be construed as exhaustive.
[0027] Numerous details are explored in the following description to provide a more thorough explanation of embodiments of the invention; however, it will be apparent to those skilled in the art that embodiments of the invention may be practiced without these specific details.
[0028] To further understand the present invention, the following embodiments are provided. It is worth noting that, unless otherwise specified, all raw materials used in the present invention are commercially available; and all methods and equipment employed are common in the art.
[0029] Example 1 A method for preparing a PVDF-based composite solid polymer electrolyte for use in lithium metal battery systems, the specific steps of which are as follows: (1) Add 0.4g of polyvinylidene fluoride (PVDF) (Shanghai Maclean Biochemical Technology Co., Ltd.) to 15mL of N,N-dimethylformamide (DMF) agent (Shanghai Adamas Reagent Co., Ltd.), and stir magnetically at room temperature or 60℃ until completely dissolved to obtain a homogeneous and transparent PVDF solution; (2) Weigh 0.028g of niobium selenide (NbSe2) layered material (Shanghai Adamas Reagent Co., Ltd.), add it to the above PVDF solution, and use ultrasonic dispersion treatment for 60 min to make niobium selenide uniformly dispersed in the polymer system to form a stable composite dispersion system; (3) Add 0.267g of lithium salt electrolyte to the above composite solution. The lithium salt is lithium bis(fluorosulfonyl)imide (LIFSI) (Shanghai Adamas Reagent Co., Ltd.). Add and stir continuously until completely dissolved to obtain a homogeneous precursor solution. (4) The above precursor solution was coated onto a polytetrafluoroethylene substrate by casting. The solvent was allowed to evaporate at room temperature, and then vacuum dried at 60°C for 12 h to finally obtain a PVDF / NbSe2 composite solid polymer electrolyte membrane with a thickness of about 0.1 mm. After removing the solvent, a self-supporting solid electrolyte film was formed and cut into discs with a diameter of 18 mm for later use.
[0030] To systematically evaluate electrolyte performance, the following test cells were assembled: 1. Using stainless steel (SS) as the blocking electrode, SS||SS symmetrical cells were assembled, and their lithium-ion conductivity was tested by AC impedance method. 2. An SS||Li half-cell was assembled using stainless steel as the working electrode and lithium metal as the counter electrode, and its electrochemical stability window was determined by linear sweep voltammetry (LSV). 3. Assemble a Li||Li symmetric cell and investigate the interfacial stability and long-term cycling performance between the electrolyte and the lithium metal anode.
[0031] Positive electrode preparation: 811 ternary positive electrode material (D50 = 3.77 μm), conductive carbon black, and polyvinylidene fluoride (PVDF5130) binder (Dongguan Kelude Experimental Equipment Technology Co., Ltd.) were uniformly mixed at a mass ratio of 8:1:1. An appropriate amount of N-methylpyrrolidone (NMP) was added to prepare a slurry. This slurry was uniformly coated onto the surface of an aluminum foil current collector. After vacuum drying for 24 hours, the slurry was cut into sheets to obtain the corresponding positive electrode plates. The positive electrode plate loading was approximately 0.2 mg / cm³. -2 .
[0032] Full cell assembly: A lithium metal sheet is attached to one side of the solid electrolyte disc prepared in Example 1 as the negative electrode; then the lithium iron phosphate or 811 positive electrode sheet prepared above is coated on carbon-coated aluminum foil, and the outer shell components are stacked in sequence and encapsulated in a glove box to obtain a solid lithium metal full cell.
[0033] Example 2 The only difference between this embodiment and Example 1 is that the amount of niobium selenide added is adjusted to 0.015 g. Everything else is the same as in Example 1.
[0034] Example 3 The only difference between this embodiment and Example 1 is that the amount of niobium selenide added is adjusted to 0.044 g. Everything else is the same as in Example 1.
[0035] Comparative Example 1 The only difference between this embodiment and Example 1 is that niobium selenide filler is not added; all other raw materials, preparation methods, and battery assembly processes are the same as in Example 1.
[0036] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the niobium selenide (NbSe2) sample in the PVDF / NbSe2 composite material from Example 1. Figure 1 It can be seen that the diffraction peak positions of the NbSe2 sample correspond exactly to the characteristic peaks of the hexagonal 2H-NbSe2 in the standard card PDF#18-0921.
[0037] Specifically, a series of clear diffraction peaks appeared at approximately 13.6°, 33.0°, 38.6°, 43.7°, 49.7°, and 58.3°, corresponding to the (002), (100), (103), (110), (105), and (201) crystal plane diffraction peaks of 2H-NbSe2, respectively. The positions of these diffraction peaks are highly consistent with the typical crystal structure characteristics of NbSe2 in the standard card, indicating that the prepared sample is a well-crystallized layered hexagonal NbSe2.
[0038] Meanwhile, in the XRD pattern of the PVDF / NbSe2 composite system, the characteristic diffraction peaks of NbSe2 remain clearly visible, indicating that niobium selenide was successfully introduced into the polymer matrix and its crystal structure remained intact during the composite process. Furthermore, the intensity of some diffraction peaks of PVDF in the composite material is weakened, suggesting that the introduction of NbSe2 has a certain perturbation effect on the PVDF crystal structure, indirectly proving the strong interfacial interaction between NbSe2 and the polymer matrix.
[0039] The above results collectively demonstrate that niobium selenide was successfully introduced into the PVDF matrix and maintained its stable layered crystal structure, providing a structural basis for the subsequent construction of efficient ion transport channels and interface regulation.
[0040] Figure 2 These are SEM images obtained from scanning electron microscopy analysis of Example 1 and Comparative Example 1. From... Figure 2 As can be seen, the structure of NSs can be well maintained by blending the electrolyte with PVDF. NSs are uniformly dispersed to form a dense structure, in which PVDF spherulites exhibit strong adhesion to NSs due to interactions. In contrast, the PVDF electrolyte exhibits a porous structure due to phase separation between the polymer and the solvent.
[0041] Figure 3 This is a graph showing the variable rate performance of the full cell in Example 1. From... Figure 3 As can be seen, at discharge rates of 0.1C, 0.5C, 1C, 2C, and 5C, Example 1 exhibits the highest discharge specific capacity of 191 mAh / g, 173 mAh / g, 161 mAh / g, 145 mAh / g, and 105 mAh / g, respectively, demonstrating excellent rate performance.
[0042] Figure 4 Example 1, Li|PVDF-NbSe2|NCM811|Li, and Comparative Example 1, Li|PVDF|NCM811|Li, were subjected to long-term cycling performance tests at 30°C using 2C. Regarding long-term cycling stability, the Li|PVDF-15|NCM811 battery retained 97.08% of its capacity after at least 500 cycles at 2C. Conversely, the PVDF-containing battery experienced a rapid capacity decrease after 200 cycles. Figure 5 This is attributed to slower lithium-ion transport and uneven lithium deposition.
[0043] Figure 6 Example 1 shows a Li||Li battery using a PVDF-NbSe2 electrolyte at 0.1 mA cm⁻¹. -2 The constant-current cycling curve at current density. From Figure 6As can be seen, the PVNS-15 system maintained a low and stable polarization overpotential throughout the 500-hour cycling process, and no obvious voltage instability was observed.
[0044] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a composite polymer solid electrolyte material, characterized in that, The method includes: mixing niobium selenide, a polymer, and a lithium salt in a solvent, coating, and drying to obtain a composite polymer solid electrolyte material.
2. The method for preparing the composite polymer solid electrolyte material according to claim 1, characterized in that, The polymer is at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, or polyacrylate.
3. The method for preparing the composite polymer solid electrolyte material according to claim 1, characterized in that, The mass ratio of niobium selenide, polymer, and lithium salt is (0.01~0.4):1:0.
028.
4. The method for preparing the composite polymer solid electrolyte material according to claim 1, characterized in that, The lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bisfluorosulfonylimide, lithium hexafluorophosphate, lithium difluorooxalate borate, lithium difluorophosphate, and lithium tetrafluoroborate.
5. The method for preparing the composite polymer solid electrolyte material according to claim 1, characterized in that, The solvent is selected from at least one of tetrahydrofuran, acetonitrile, N,N-dimethylformamide, or N-methylpyrrolidone.
6. The method for preparing the composite polymer solid electrolyte material according to claim 1, characterized in that, The coating includes scraping or casting.
7. The method for preparing the composite polymer solid electrolyte material according to claim 1, characterized in that, The drying process employs vacuum drying at a temperature of 50-80℃ for a duration of 12-48 hours.
8. A composite polymer solid electrolyte material, characterized in that, It is prepared by the method described in any one of claims 1 to 7.
9. An application of the composite polymer solid electrolyte material as described in claim 8, characterized in that, The composite polymer solid electrolyte material is used to prepare solid metal batteries.
10. The application of the composite polymer solid electrolyte material according to claim 9, characterized in that, The positive electrode of the solid metal battery is a lithium iron phosphate positive electrode or a nickel-cobalt-manganese ternary positive electrode; the negative electrode is one of an alkali metal negative electrode, a graphite negative electrode, a hard carbon negative electrode, a silicon-carbon negative electrode or a phosphorus material negative electrode; preferably, it is a lithium negative electrode.
Citation Information
Patent Citations
Electrolyte for compact polymer-based solid-state lithium battery
CN116130758A